Equity on the frontlines of trauma surgery: An #EAST4ALL roundtable. Issue 1 (January 2021) - Tung, Lily; Long, Andrea M.; Bonne, Stephanie; Tseng, Esther S.; Bruns, Brandon; Joseph, Bellal; Williams, Brian H.; Stein, Deborah; Freischlag, Julie A.; Goulet, Nicole; Khandelwal, Cathleen; Kiselak, Elizabeth; et al.
Abstract : BACKGROUND: Inequity exists in surgical training and the workplace. The Eastern Association for the Surgery of Trauma (EAST) Equity, Quality, and Inclusion in Trauma Surgery Ad Hoc Task Force (EAST4ALL) sought to raise awareness and provide resources to combat these inequities. METHODS: A study was conducted of EAST members to ascertain areas of inequity and lack of inclusion. Specific problems and barriers were identified that hindered inclusion. Toolkits were developed as resources for individuals and institutions to address and overcome these barriers. RESULTS: Four key areas were identified: (1) harassment and discrimination, (2) gender pay gap or parity, (3) implicit bias and microaggressions, and (4) call-out culture. A diverse panel of seven surgeons with experience in overcoming these barriers either on a personal level or as a chief or chair of surgery was formed. Four scenarios based on these key areas were proposed to the panelists, who then modeled responses as allies. CONCLUSION: Despite perceived progress in addressing discrimination and inequity, residents and faculty continue to encounter barriers at the workplace at levels today similar to those decades ago. Action is needed to address inequities and lack of inclusion in acute care surgery. The EAST is working on fostering a culture that minimizes bias and recognizes and addresses systemic inequities, and has provided toolkits to support these goals. Together, we can create a better future for all of us.